The Effect of Moral Reasoning Level and Emotional Intelligence on Employment Ethics Assessment of Earnings Management - Dewita Puspawati; Kurnia Rina Ariani; Novel Idris Abas (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
The purpose of this study is to examine the influence of moral level reasoning and emotional intelligence on the assessment of earnings management ethics. The theory used is the theory of planned behavior. Respondents in this study are S1 Accounting Department Faculty of Economics and Business University of Muhammadiyah Surakarta. The samples used were 89 respondents with convenience sampling technique. The results showed that the moral level of reasoning affect the evaluation of earnings management ethics, while emotional intelligence does not affect the dependent variable.